Impact des accords commerciaux internationaux sur la protection de l’environnement - BASHIGE BINJA Audry (IJRDO - Journal of Social Science and Humanities Research, 2025)
Today’s world is formed in industrial development, imports and exports of products and properties; global economic development has nevertheless been accompanied by a growth in environmental challenges, which risk negatively influencing well-being, development, health and economic growth itself. Our study raised the examination of the "impacts of international trade agreements on environmental protection". For the trade-environment debate, the problem of the capacity of the world trade organization to take into consideration, to manage environmental and healthy concerns arises. With an imperial approach, we have produced this article which has made it possible to complete the logicalenvironmental measurement of legal doctrine and a mobilization of data on the basis of a documentary technique with any international trade agreement as an inclusion criterion. The results obtained in this study demonstrate that trade agreements do not have negative impacts on the environment because of "international trade" which means that the right to the environment is increasingly asserted within the framework of international trade agreements. The restrictions of the multilateral agreement are a real proof that States seek at all costs to preserve the environment and the health of consumers. Therefore, the declaration of riot advocates a synergy between trade and the environment, as well as between the MEA and the CWO agreements because the protocol on substances that deplete ozone deposition seems to meet all the obligations of Article XX. Generally considered the most successful international agreement in the field of the environment. On the other hand, it observes that the relationship between multilateral environmental agreements and international trade are the main concerns 12; This provides that "States must cooperate in order to promote an open international economic system conducive to achieving economic growth and sustainable development in all countries, which would make it possible to better combat the problems of environmental degradation.